Histopathological Effect of Zinc Oxide Nanoparticles on Kkidney and Liver Tissues in Albino Male Mice - Salman, Ruqayah Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Objective: The present study investigated the effects of different dose levels of Zinc oxide Nanoparticles (ZnO NPs) on the liver and kidney tissues in albino male mice. Methadology: ZnO NPs was administrated as a daily oral dose of (150, 350 mg/kg body weight) gavage for 2 weeks. Eighteen male mices were used by dividing them into three groups. Result: Histopathological examination of kidney and hepatic tissues treated with ZnO NPs showed toxicity changes compared with control group. Conclusion:This study demonstrated the ability of ZnO NPs to affect on kidney and liver tissues. Recommendation: More study needed to know the effect of different doses of nanoparticles on human health.